Prototype Development and Validation of a Beam-Divergence Control System for Free-Space Laser Communications - Carrasco-Casado, Alberto; Shiratama, Koichi; Kolev, Dimitar; Trinh, Phuc V.; Fuse, Tetsuharu; Fuse, Shingo; Kawaguchi, Koji; Hashimoto, Yusuke; Hyodo, Masamitsu; Sakamoto, Takashi; Kunisada, Terufusa; Toyoshima, Morio (Frontiers in Physics, 2022)
Being able to dynamically control the transmitted-beam divergence can bring important advantages in free-space optical communications. Specifically, this technique can help optimizing the overall communications performance when the optimum laser-beam divergence is not fixed or unknown. This is the case in most realistic space laser communication systems, since the optimum beam divergence depends on multiple factors that can vary with time, such as the link distance, or cannot be accurately known, such as the actual pointing accuracy. A dynamic beam-divergence control allows optimizing the link performance for every platform, scenario, and condition. NICT is currently working towards the development of a series of versatile lasercom terminals that can fit a variety of conditions, for which the adaptive element of the transmitted beam divergence is a key element. This manuscript presents a prototype of a beam-divergence control system designed and developed by NICT and Tamron to evaluate this technique and to be later integrated within the lasercom terminals. The basic design of the prototype is introduced as well as the first validation tests that demonstrate its performance.